Caries and its association with infant feeding and oral health- related behaviours in 3–4-year-old Brazilian children - Dini EL, Holt RD, Bedi R (Blackwell Synergy, 2000)
To investigate the relationships between socio-demographic factors, infant feeding habits, oral hygiene and the prevalence and patterns of caries in Brazilian 3–4-year-olds. Methods: Systematic random sampling was used to select children enrolled in municipal nurseries in Araraquara, Brazil, in 1998. Clinical examinations were carried out by one examiner using dmft and dmfs indices and WHO criteria.